Attitudes and motivations towards learning English as a second language among form four students at SMK Padawan / John Tinggang Uchau - Uchau, John Tinggang (2012)
The study has two major aims, firstly, to determine the students' level of attitudes and motivation and secondly, to find out the students' motivation orientations. To assess the students' attitudes and motivations, the researcher adopted Gardner's (1985) test battery known as the Attitude and Motivation Test Battery (AMTB). It comprises 104 items which include 12 main domains namely, Interest in Foreign languages, Parental Encouragement, Motivational intensity, English class anxiety, English teacher evaluation, Attitudes towards learning English, Attitudes towards English-speaking people, Integrative orientation, Desire to learn English, English course evaluation, English use anxiety, and Instrumental Orientation. Using a survey research design, the questionnaire was distributed based on convenience sampling, to 60 Form Four students at SM Padawan, situated at the outskirt of Kuching City in Sarawak. The questionnaires returned were analysed using Statistical Package for Social Sciences (SPSS) Version 17.0 for descriptive statistics. The results indicated some positive high level on most domains reflecting that the students were generally positive. The mean scores range from as low as 1.5 to as high as 5.7 against the 6-point likert scale. The integrative orientation domain shows mean scores of 5.58 (SD= .849) for item 8 which is very high against the 6-point scale. Overall, the study has revealed that the attitudes and motivations of Form 4 students involved were generally positive towards the English language.